Nursing Diagnosis in Home Care: Audit Tool Development - Zink, M.R. (Journal of Community Health Nursing, 1994)
Little research has been done to document the value of using nursing diagnosis in home care and the impact that increased acuity levels have had in diagnostic selection. Nursing diagnosis documentation in home care was examined to see whether it had a relation to select client and visit pattern variables. This retrospective chart audit, which piloted a newly developed instrument called the Home Care Audit Tool, utilized a sample of 199 closed records of a large midwestem Visiting Nurse Association. The mean age of the client population was 76 years, with 64% female. There were 269 initial nursing diagnoses cited in the sample records, averaging 1.75 diagnoses per case. The number of recorded visits increased when select nursing diagnoses were cited together in a single case. © 1994, Taylor & Francis Group, LLC. All rights reserved.
5 citations (Crossref) [2023-10-31]
Keywords: Aged; Community Health Nursing; Female; Home Care Services; Human; Male; Models; Nursing; Nursing Audit; Nursing Diagnosis; Nursing Records; Pilot Projects; Reproducibility of Results; Retrospective Studies; Severity of Illness Index; article; community care; dept.nur; home care; medical assessment; nursing; nursing education

Nursing ethics committees —where are they? - Zink, M.R.; Titus, L. (Nursing Management, 1994)
When establishing Nursing Ethics Committees (NECs), statewide nursing organizations play an important role in developing and disseminating resources. The Connecticut Nurses Association Ethics and Human Rights Committee surveyed 85 healthcare facilities to identify active NECs. Representatives facilitated other committees by providing guidelines and assistance to those agencies developing NECs — the ultimate goal. © 1994 by Springhouse Corporation.
2 citations (Crossref) [2023-10-31]
Keywords: Bioethics and Professional Ethics; Clinical Approach/Source; Connecticut; Empirical Approach; Ethics Committees; Ethics Committees; Clinical; Ethics; Nursing; Human; Patient Advocacy; Questionnaires; Survey; United States; article; dept.nur; human; human rights; medical ethics; organization and management; professional standard; questionnaire; survey